Computational Collective Intelligence. Technologies and Applications Second International Conference, ICCCI 2010, Kaohsiung, Taiwan, November 10-12, 2010. Proceedings, Part III - Pan, Jeng-Shyang.; Chen, Shyi-Ming.; Nguyen, Ngoc Thanh; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The three-volume set LNAI 6421, 6422 and 6423 constitutes the refereed proceedings of the Second International Conference on Computational Collective Intelligence, ICCCI 2010, held in Kaohsiung, Taiwan, in November 2010. Based on rigorous peer reviews, the program committee carefully selected 155 revised papers from 500 submissions for presentation in three volumes. The papers are organized in topical sections on collective intelligence in web systems - web systems analysis; intelligent computing for data security; smart clustering techniques; web service; quantitative management of technology; agent system; CCI-based optimization models; fuzzy logic and its applications; social networks; innovations in computation and application; intelligent signal processing for human-machine interaction; novel approaches to intelligent applications; intelligent technologies for medical related applications; novel approaches to collective computations and systems; intelligent systems; advanced knowledgement management; intelligent computing for image analysis; intelligent digital watermarking and pattern recognition; innovative information system and application; intelligent computing for networks; soft computing to industrial management and applications; innovations in pervasive computing; biological computing.
Keywords: Computer science; Computer Communication Networks; Computer software; Data mining; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Computer Communication Networks; Data Mining and Knowledge Discovery; Algorithm Analysis and Problem Complexity; User Interfaces and Human Computer Interaction